Fixed‑bed adsorption for industrial wastewater purifcation: an in‑depth review - Rajandran, Prabu; Nasratun, Masngut; Nor Hasmaliana, Abdul Manas; Nur Izyan, Wan Azelee; Siti Fatimah Zaharah, Mohamad Fuzi; Mohamad Abd Hadi, Bunyamin (Springer Berlin Heidelberg, 2025)
The increasing discharge of industrial wastewater contaminated with hazardous pollutants requires innovative and efficient treatment technologies. This review addresses the potential of fixed-bed adsorption systems for the effective removal of a wide spectrum of contaminants from industrial effluent. It explains the basic principles, characteristics and mechanisms of fixed-bed adsorption systems and examines important factors affecting their performance. Through a comparative analysis of different adsorption models, the paper provides insights into the efficiency and applicability of these models in assessing the characteristics of adsorption system using breakthrough curves. The findings advocate for policy support to integrate fixed-bed adsorption technologies into existing wastewater management systems to improve environmental protection and public health